1994
DOI: 10.2166/wst.1994.0436
|View full text |Cite
|
Sign up to set email alerts
|

Membrane bioreactor treatment of oily wastes from a metal transformation mill

Abstract: The performance of a membrane bioreactor treating wastewater from a metal transformation industry was compared with the ultrafiltration system at the mill. Toxicity analysis using the microtox and algal tests on the untreated and treated effluents from both systems showed a 130 fold reduction in toxicity due to the ultrafiltration step and a further 10 fold reduction due to the biological step. This resulted in a biomass which must be disposed of as a hazardous waste. In comparison with the present situation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The study of metals in wastewater, as they relate to MBRs, largely falls into three groups: a) use of metal-based coagulants for anti-fouling, 79 b) treatment of metals-laden industrial effluents, [80][81][82] and c) fate of metal micropollutants in municipal and industrial wastewater treatment. 83,84 An advantage of an MBR is its ability to operate with uncoupled hydraulic and solids retention times (HRT and SRT respectively).…”
Section: Membrane Bioreactors and Metals In Wastewater Treatmentmentioning
confidence: 99%
“…The study of metals in wastewater, as they relate to MBRs, largely falls into three groups: a) use of metal-based coagulants for anti-fouling, 79 b) treatment of metals-laden industrial effluents, [80][81][82] and c) fate of metal micropollutants in municipal and industrial wastewater treatment. 83,84 An advantage of an MBR is its ability to operate with uncoupled hydraulic and solids retention times (HRT and SRT respectively).…”
Section: Membrane Bioreactors and Metals In Wastewater Treatmentmentioning
confidence: 99%
“…The interest of using MBR instead of classical activated sludge system for the treatment of industrial wastewater was demonstrated [ 6 , 7 ]. Zhao et al [ 8 ] used a laboratory-scale anaerobic/anoxic/oxic membrane bioreactor system to treat heavily loaded and toxic coke plant wastewater and operated for more than 500 days.…”
Section: Introductionmentioning
confidence: 99%
“…HRT for MBR applications in industrial wastewater treatment ranged from 10 hours (62 days SRT} for pharmaceutical effluents with 63-86% COD removal (Benitez et al, 1995) to 24 hours (both 10 and 550 days SRT) for tannery wastewaters with 94% COD removal (Yamamoto and Win, 1991). For oily wastewater, Zaloum et al (1994) reported 99.6% BOD and 73% NH3-N removal using an HRT of 240 hours (75 days SRT) while, for landfill leachate, Ahn and Song. (1999) reported 99.6% BOD and 90% COD removal using an HRT of 240 hours (30 days SRT).…”
Section: Hydraulic Retention Time (Hrt)mentioning
confidence: 99%
“…In addition, because of the density of oil and its ability to emulsify, conventional settling tanks are generally not very effective. Among the available physicochemical treatment methods, ultrafiltration is perhaps most advantageous for treatment of oil-water emulsions (Lipp et al, 1988), Membranes, especially ultrafilters, were initially used as a standard process to reduce the volume of oily wastewater by separating the oily matter from water (Zaloum et al, 1994). Lee et al (1994) reduced the volume of oily waste 10 times while Leikness and Semmens (2000) concentrated the oil emulsion by 5 times with ultrafiltration.…”
Section: Oily Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation